The effects of blood flow restriction training on PAP and lower limb muscle activation: a meta-analysis - Wang, Jian; Liu, Haiyang; Jiang, Lizhu (Frontiers in Physiology, 2023)
Objective:To systematically evaluate the effects of Blood Flow Restriction Training (BFR) on lower limb muscle activation and Post-Activation Potentiation (PAP) of athletes based on Meta-analysis, and discuss methods to improve instant muscle strength, so as to provide reference for training in this field. Methods: Randomized Controlled Trials (RCTs) examining the impact of BFR on muscle activation and PAP were gathered through database searches, including CNKI, WAN-FANG, Web of Science, PubMed, and others. The Cochrane risk of bias tool was used to include and exclude literature. Quality evaluation and statistical analysis were conducted using Revman 5.3, Stata 16.0, and other software. Sensitivity analysis and funnel plots were employed to assess result stability and publication bias. Results:18 literatures were included with a total of 267 subjects. Meta-analysis showed that BFR could significantly improve the RMS value of lower limb muscles [SMD=0.98, 95%CI (0.71,1.24), P < 0.00001]. BFR had a significant effect on the immediate explosive power of lower limbs [SMD=0.28, 95%CI (0.02,0.53), P=0.03], but the heterogeneity was obvious (I2=51%). Subgroup Analysis showed that different training methods may be the influencing factor leading to the heterogeneity between studies. The measurement indexes were Counter Movement Jump(CMJ) [SMD=0.45, 95%CI (0.20, 0.69), P=0.0004], the training mode was to overcome the body weight [SMD=0.57, 95%CI (0.33,0.82), P<0.00001], and the compressive strength of 40%~60%AOP[SMD=0.57, 95%CI (0.31, 0.83), P<0.0001) reached the maximum effect and was statistically significant. Conclusion:BFR training can induce lower extremity muscle activation and PAP. Combining self-weight training with BFR exercises set at 40%-60% AOP appears to be particularly effective in inducing PAP, especially for enhancing Counter Movement Jump (CMJ). Furthermore, combing body-weight training with BFR is considered an effective warm up method to improve CMJ.